Non-dermatological challenges of chronic itch - Kremer, Andreas; Mettang, Thomas; Weisshaar, Elke (Acta dermato-venereologica, 2020)
Chronic itch occurs in many skin diseases, but also in a variety of systemic, neurological, and psychogenic/psychosomatic disorders, or is caused by drug intake. When several diseases or causes co-exist, chronic itch is categorized as "mixed origin". These patients present with unaltered skin or with chronic scratch lesions including chronic prurigo. Precise diagnostics are necessary to evaluate the underlying aetiology, to enable identification of the best treatment available, and to improve patients' quality of life. This is of particular relevance in elderly people in whom chronic itch is often of systemic or mixed origin. Xerosis cutis is a frequent cofactor contributing to chronic itch of non-dermatological origin. Treatment is frequently multimodal, considering age, comorbidities, current drug intake, quality and intensity of itch. With regard to the demographic situation of the population, characterized by increasing life expectancy and polypharmacy, itch of non-dermatological origin will represent an increasing medical challenge in the future.